2020
DOI: 10.21203/rs.3.rs-96272/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural Correlates of the Impulse Dyscontrol Domain of Mild Behavioral Impairment

Abstract: Background: Agitation and aggression are common in dementia and pre-dementia. The dementia risk syndrome mild behavioral impairment (MBI) includes these symptoms in the impulse dyscontrol domain. However, the neural circuitry associated with impulse dyscontrol in neurodegenerative disease is not well understood. The aim of this work is to investigate if regional micro- and macro-structural brain properties are associated with impulse dyscontrol symptoms in older adults with normal cognition, mild cognitive imp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…They are associated with neurodegenerative change and progressive cognitive decline, and have predictive utility in CN and MCI subjects 22 . Impulse dyscontrol is common in advance of dementia, and is an MBI domain that is clinically meaningful 23–25 . Socially inappropriate behaviours are frequent in prodromal AD 26 .…”
Section: Introductionmentioning
confidence: 99%
“…They are associated with neurodegenerative change and progressive cognitive decline, and have predictive utility in CN and MCI subjects 22 . Impulse dyscontrol is common in advance of dementia, and is an MBI domain that is clinically meaningful 23–25 . Socially inappropriate behaviours are frequent in prodromal AD 26 .…”
Section: Introductionmentioning
confidence: 99%
“…reported that impulse dyscontrol was strongly correlated with atrophy of mesial temporal regions, which have been early implicated in the trajectory of AD. And another recent study conducted by Gill et al 49 . detected association of impulse dyscontrol with changes of white matter integrity in tracts including the cingulum, fornix, superior fronto‐occipital fasciculus, and uncinate fasciculus.…”
Section: Discussionmentioning
confidence: 93%
“…MBI has several biological correlates, which the literature is just beginning to explore. Known associations exist between MBI and biological markers of AD, including Aβ-positron emission tomography (PET), 16 cerebrospinal fluid (CSF) tau and tau-PET, 38,39 white matter atrophy, 40,41 grey matter atrophy, 42,43 plasma neurofilament light (NfL), 15 and AD risk gene loci. 44,45 The current study extends the literature on the biological basis of MBI.…”
Section: Discussionmentioning
confidence: 99%
“…Several longitudinal studies have identified emergent impulse dyscontrol symptoms among the earliest behavioural changes associated with incident cognitive decline and dementia. 31,61,62 Two studies found that impulse dyscontrol symptoms were comparable to hippocampal atrophy for prognostication of cognitive decline and dementia, 41,63 associated with both grey and white matter changes in advance of dementia. 40 Thus, the link between AD biomarkers and MBI subdomains can be challenging to interpret, and further investigation is required to explore these relationships.…”
Section: Discussionmentioning
confidence: 99%